Social factors and preference for quality cues: Towards a social construction of wine quality. (August 2020) - Lo Monaco, Gregory; Tavani, Jean Louis; Codaccioni, Colomba
Graphical abstract: Highlights: This research highlights a social construction of wine quality. Evidence of a structural homology concerning choices of wine quality cues. Effects of sex and socio-economic status on the choice of wine quality cues. Abstract: Wine preferences and perceived related quality have led researchers to consider the choice strategies employed by consumers. This article proposes to address the question of the effect of the position occupied in the social space (e.g., socially dominated vs. socially dominant individuals) on the selection of cues for evaluating the quality of red and rosé wines. Participants were asked to fill out a questionnaire in the wine section of supermarkets located in the south of France. Taken as a whole, the results confirm our hypotheses. Via a Guttman effect in principle component analysis and contrast analyses, they tend to show a structural homology effect in relation to quality cue preferences. From a socio-psychological point of view, dominants express preferences for cues reflecting their knowledge of the product. By contrast, socially dominated individuals are more sensitive to the cues related to the aesthetic dimension of the product. The results are discussed in terms of the conceptualization of intrinsic vs. extrinsic cues.